Microbial colonization history modulates anxiety-like and complex social behavior in mice. (July 2021) - Kamimura, Itsuka; Kaneko, Ryou; Morita, Hidetoshi; Mogi, Kazutaka; Kikusui, Takefumi
Highlights: Lower sociality and higher anxiety in GF mice transferred to SPF room. Gene expression in GF mice transferred to SPF room was significantly different from SPF mice. Microbiome composition became similar between GF and SPF mice when cohabitating. Microbiome composition affects neurobehavioral responses and sociality. Abstract: Microbiome composition has a pivotal role in neurobehavioral development. However, there is limited information about the role of the microbiome in sociability of mice in complex social contexts. Germ-free (GF) mice were reared in a microbiota-free environment until postnatal day 21 and then transferred to a room containing specific pathogen free (SPF) mice. At 9 weeks old, group social behaviors were measured for three GF mice and three SPF mice unfamiliar to each other. GF mice spent less time in the center area of the arena and there were longer inter-individual distances compared with SPF mice. GF mice also had decreased brain-derived neurotrophic factor (BDNF) and increased ΔFosB mRNA in the prefrontal cortex compared to SPF mice. There were differences in the gut microbiome composition between GF and SPF mice; however, if cohabitating after weaning, then their microbiome composition became equivalent and group differences in behavior and BDNF and ΔFosB mRNA expression disappeared. These results demonstrate that the bacterial community can modulate neural systems that are involved in sociability and anxiety during the developmental period and suggest that sociability and anxiety can be shaped depending on the microbiome environment through interaction with conspecifics.